Safety of Recombinant Zoster Vaccine in Patients with Inflammatory Bowel Disease. (29th March 2022) - Khan, Nabeel; Trivedi, Chinmay; Aberra, Faten; Pernes, Tyler; Yang, Yu-Xiao
Abstract: Background and Aims: Patients with inflammatory bowel disease [IBD] have an increased risk of contracting herpes zoster [HZ] infection. However, vaccination rates for HZ are low among IBD patients. A contributing factor may be fear of an IBD flare associated with vaccination. Our aim here was to evaluate if recombinant zoster vaccine [RZV] is associated with an IBD flare. Methods: This was a retrospective cohort study using data from the Veterans Affairs Healthcare System [VAHS]. The exposure of interest was receiving RZV. We randomly matched such exposed patients with unexposed individuals. The primary outcome was the first episode of IBD flare within 90 days of the index date. Baseline characteristics were compared between groups using a t -test for continuous variables and Chi-square test for categorical variables. Conditional logistic regression was used to estimate the odds ratio [OR] and 95% confidence interval [CI]. Results: Among the eligible study cohort, 1677 patients received RZV. Thirty-six patients, 20 in the exposed group and 16 in the unexposed group, had a confirmed flare by chart review. The 90-day cumulative incidence of IBD flare was not different between the vaccinated and unvaccinated groups [1.2% among those exposed vs 1.0% among those unexposed, p = 0.503]. The OR for IBD flare associated with RZV vaccination was 1.25 [95% CI: 0.65–2.41]. Conclusion: In a nationwide cohort of stable IBD patients, administration of RZV was not associated with the risk of IBD flare within 90 days. These findings should motivate further use of this highly effective vaccine.